RISK MEASURE ON FINANCE ASSETS AND INSURANCE PRODUCT AS THE BASIS FOR PORTFOLIO SELECTION - ARDI PRADANA (NIM:10114038), MUHAMMAD
Risks are disadvantages that could happen of an ongoing process or future event. Risks in a company is generally divided by two i.e. financial asset risks and insurance product risks. Those risks has to be minimized, but has to be quantified first by risk measure. Risk measures that can be used are Value-at-Risk (VaR) and prediction inteval, VaR that will be used in this final project are VaR weighted mean quantile based (QVaR) and expectile based (EVaR), prediction interval is used to get coverage probability by minimizing utility function. Risks can be minimized by weighting each risks or make a portfolio. Weighting risks in portfolio can affect its risk measure so the weight has to be chosen that causing risks in portfolio minimized, Lorenz curve can be used as risk measure in selecting portfolios.